Impacts of The POGIL Learning Model Combined With a SETS Approach on Chemical Literacy and Science Process Skills in The Context of Buffer Solutions - Putri Anggun Puspitasari; Budi Hastuti; Bakti Mulyani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
This study evaluates the impact of the Process Oriented Guided Inquiry Learning (POGIL) model combined with a Science-Technology-Society-Environment (SETS) approach on chemical literacy and science process skills within buffer solutions. Employing a quasi-experimental design with a nonequivalent control group, the research involved 71 students divided into experimental and control groups. Cluster random sampling was utilized for participant selection, and Multivariate Analysis of Variance (MANOVA) was applied to test the hypotheses. The findings reveal a significant effect of the POGIL learning model integrated with a SETS approach on simultaneously enhancing students' chemical literacy and science process skills. This outcome is substantiated by the MANOVA results, which indicate a significance level of 0.000, falling below the threshold of 0.05, thereby leading to the rejection of the null hypothesis (H0). Notably, the experimental group demonstrated significant improvements compared to the control group. Chemical literacy in the experimental group reached 79.90%, significantly higher than the 62.53% observed in the control group. Additionally, the N-gain scores for the experimental and control groups were 0.70 and 0.32, respectively, categorized as high and medium. Furthermore, the percentages of science process skills were 91.61% in the experimental group and 82.37% in the control group, both in the very good category. These results underscore the effectiveness of combining POGIL with a SETS approach in elevating chemical literacy and science process skills, suggesting this method is a potent educational tool in chemical education.